Kontrol Diri dan Tekanan Teman Sebaya (Peer Pressure) dengan Kenakalan Remaja pada Kalangan Remaja Kelurahan Klender - Nathaline, Grace; J. Silaen, Sondang Maria (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This research is a quantitative study which aims to examine the relation between selfcontrol and negative peer pressure with juvenile delinquency among adolecents of Kelurahan Klender. The subjects in this study were 64 adolescents as a sample with the method of data collection using multistage random sampling techniques. Measuring instruments used were juvenile delinquency scale, self-control scale, and negative peer pressure scale. The results showed that there was a significant negative relation between self-control and juvenile delinquency for -0756, and there was a significant positive relation between negative peer pressure and juvenile delinquency for 0,815. Furthermore, the results of data analysis with multivariate correlation using the SPSS (Statistical Product and Service Solution) computer program version 26.0 for windows obtained the correlation coefficient R = 0,829. From the results of this study it can be concluded that the lower self-control, the higher juvenile delinquenc, and then, the higher negative peer pressure, the higher juvenile delinquency. Keywords : Juvenile Delinquency, Self-Control, Negative Peer Pressure.